Portable and Efficient Fingerprint Authentication System Based on a Microcontroller - Mauricio García Vargas; Fredy Edimer Hoyos; John Edwin Candelo (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents the design of a fingerprint authentication system based on a simple microcontroller and the fingerprint sensor. The circuit diagram and details regarding the procedure are included. The system was programed in MPLAB and then embedded into the microcontroller. Communication between the PIC and sensor is by RS232 protocol. The results show that the system recognizes the fingerprint in less than 1 second. It is portable and there is no need for image processing. Furthermore, the system shows a high effectiveness when storing and verifying fingerprints.